Identification of areas of permanent preservation of water courses of the city of Boa Vista (RR) and aspects of environmental legislation - Ignácio, Rozane Pereira; Silva, Edson Vicente da; Carvalho, Thiago Morato; Silva, Carmem Lúcia Rosa da (Revista Hipótese, 2017)
This study aimed to characterize in a first approximation the Permanent Preservation Areas of urban streams in the city of Boa Vista (RR). They were used RapidEye images, aerial photography and Geoeye 1943 for delimitation of the urban area, identification and mapping of streams and their respective PPAs, as well as morphometric characterization of the urban drainage network.